Pelayanan Tenaga Administrasi Sekolah Urusan Persuratan dan Pengarsipan Berbasisi Teknologi Informasi di SMK se-Kota Payakumbuh - Desi Tri Triana; Rusdinal Rusdinal; Jasrial Jasrial; Lusi Susanti (Universitas Negeri Padang, 2021)
This research is motivated by the observations and interviews of the authors of several teachers at SMKN 1 Padang that showed that the school administration services for surveying and archiving based on information technology have not been good. The research aims to obtain information on Administrative Personnel Services School of Research Affairs and Information Technology-Based Archiving as seen from the aspects of (1) Physical Evidence, (2) Reliability, (3) Response. This study is descriptive quantitative with a population of all 458 teachers in vocational schools in Payakumbuh City. While the sample size was taken using Slovin formula with a 10% error rate using Proportional Random Sampling techniques ratified by 82 teachers. The assessment instrument is a Likert scale questionnaire with five alternative answers. The results showed the ministry of administrative personnel services school administration affairs surveying and archiving based on information technology from aspects tangible (physical evidence) with a good category average score of 4.20, school administration services for surveying and archiving based on information technology from reliability aspects (reliability) is in a good position with an average score of 4.09, school administration services survey affairs and information technology-based archiving from responsiveness aspects (responsiveness) has been carried out well at the level of 4.00. From the whole, it can be concluded that the ministry of school administration of research and archiving based on information technology in smk in Payakumbuh City has been carried out well with the acquisition of the number 4.10.This research is motivated by the observations and interviews of the authors of several teachers at SMKN 1 Padang that showed that the school administration services for surveying and archiving based on information technology have not been good. The research aims to obtain information on Administrative Personnel Services School of Research Affairs and Information Technology-Based Archiving as seen from the aspects of (1) Physical Evidence, (2) Reliability, (3) Response. This study is descriptive quantitative with a population of all 458 teachers in vocational schools in Payakumbuh City. While the sample size was taken using Slovin formula with a 10% error rate using Proportional Random Sampling techniques ratified by 82 teachers. The assessment instrument is a Likert scale questionnaire with five alternative answers. The results showed the ministry of administrative personnel services school administration affairs surveying and archiving based on information technology from aspects tangible (physical evidence) with a good category average score of 4.20, school administration services for surveying and archiving based on information technology from reliability aspects (reliability) is in a good position with an average score of 4.09, school administration services survey affairs and information technology-based archiving from responsiveness aspects (responsiveness) has been carried out well at the level of 4.00. From the whole, it can be concluded that the ministry of school administration of research and archiving based on information technology in smk in Payakumbuh City has been carried out well with the acquisition of the number 4.10.